Pop-up book Putri Tujuh to improve the ability to read aloud - Rizka Ardini; S. Safran (Inovasi Kurikulum, 2024)
This study aims to develop an interactive learning medium in the form of a pop-up book titled Putri Tujuh to enhance the reading-aloud ability of third-grade students at SD Negeri 057751 Simpang UPL. The study followed the ADDIE development model, which involved five stages. Firstly, the analysis stage revealed the need for more engaging learning media. Secondly, the design stage focused on creating a pop-up book design using simple materials as an interactive learning tool. Thirdly, the development stage involved validation by material and language experts, resulting in a high feasibility rating. Fourthly, the implementation stage included an effectiveness test that showed a significant improvement in reading skills and a practicality test that indicated the media's usefulness. Finally, the evaluation stage concluded that the product did not require further improvement based on the positive results of the tests conducted. The media effectively increased students' reading-aloud skills and reading interests. The implications of this research suggest that the use of pop-up books can be an effective alternative in teaching reading aloud in elementary schools, providing a solution to increase student motivation and engagement and assisting teachers in delivering more interactive and engaging learning materials. AbstrakPenelitian ini bertujuan untuk mengembangkan media pembelajaran interaktif berupa buku pop-up berjudul Putri Tujuh untuk meningkatkan kemampuan membaca nyaring siswa kelas III SD Negeri 057751 Simpang UPL. Penelitian ini mengikuti model pengembangan ADDIE yang meliputi lima tahap. Pertama, tahap analisis mengungkapkan perlunya media pembelajaran yang lebih menarik. Kedua, tahap desain difokuskan pada pembuatan desain buku pop-up sebagai alat pembelajaran interaktif dengan menggunakan bahan ajar sederhana. Ketiga, tahap pengembangan melibatkan validasi oleh ahli materi dan bahasa, menghasilkan peringkat kelayakan yang tinggi. Keempat, tahap implementasi meliputi uji efektivitas yang menunjukkan peningkatan keterampilan membaca yang signifikan, serta uji praktikalitas yang menunjukkan kegunaan media. Terakhir, tahap evaluasi menyimpulkan bahwa produk tidak memerlukan perbaikan lebih lanjut berdasarkan hasil positif dari uji yang dilakukan. Media efektif meningkatkan keterampilan membaca nyaring dan minat baca siswa. Implikasi dari penelitian ini menunjukkan bahwa penggunaan buku pop-up dapat menjadi alternatif yang efektif dalam pengajaran membaca nyaring di sekolah dasar, memberikan solusi untuk meningkatkan motivasi dan keterlibatan siswa, serta membantu guru dalam menyampaikan materi pembelajaran yang lebih interaktif dan menarik.Kata Kunci: buku pop-up; cerita rakyat; membaca nyaring